Imagination and participation : next steps in public library architecture - Sternheim, Joyce; Bruijnzeels, Rob; Tee, Jane (Rotterdam : nai010 Publishers, 2021)
How can the public library fulfill its classic social mission in our individualized and sometimes fragmented society? And how does such a library fit into the urban public space, in which commerce and consumption seem to reign supreme? This requires innovative architecture, the strength of imagination and the willingness to think countercyclically. In 'Imagination and Participation' librarians Rob Bruijnzeels and Joyce Sternheim examine the most important transitions in public library work. They spoke with experts and Dutch top architects who have designed public libraries in the Netherlands and abroad. These conversations and the authors' own insights and experiences have resulted in a new perspective on contemporary library work that has been translated into starting points for the future architecture of public libraries. The authors have been working on the transition of library work and its consequences for the architecture and design of library buildings for quite some time. They are members of the Ministerie van Verbeelding, 'Ministry of Imagination', a design collective that previously designed a number of notable libraries.
"How can the public library fulfill its classic social mission in our individualized and sometimes fragmented society? And how does such a library fit into the urban public space, in which commerce and consumption seem to reign supreme? This requires innovative library work and architecture, the strength of imagination and the willingness to think countercyclical. In 'Imagination and Participation' librarians Rob Bruijnzeels and Joyce Sternheim examine the most important transitions in public library work. They spoke with experts and Dutch and Flemish top architects who have designed public libraries in the Netherlands and abroad. These conversations and the authors own insights and experiences have resulted in a new perspective on contemporary library work that has been translated into starting points for the future architecture of public libraries. The authors have been working on the transition of library work and its consequences for the architecture and design of library buildings for quite some time. They are members of the Ministerie van Verbeelding, 'Ministry of Imagination', a design collective that has designed a number of notable libraries. Includes projects and conversations with leading Dutch and Flemish architects a.o: Jo Coenen, Chris van Duijn, Francine Houben, Winy Maas, Vincent Panhuysen and Michiel Riedijk."--Page 4 of printed paper wrapper.
Transition -- Value -- Typology -- Participation -- Inspiration -- Imagination.
Translator statement of responsibility from page 224.
"... to get more information about typologies, the sources we used, the libraries we mention and the architects we spoke with ... go to: www.imaginationandparticipation.com "--Page 3.
Keywords: Library architecture; Library architecture -- Pictorial works; Public libraries -- Space utilization; Public libraries -- Aims and objectives; Public libraries -- Design and construction